On production ultrashort- and short-lived isotopes for nuclear medicine at cyclotron CV-28 - Petrusenko, Yu.T.; Nikolaichuk, L.I.; Tutubalin, A.I.; Shepelev, A.G.; Ponomarenko, T.A.; Nemashkalo, O.V. (Вопросы атомной науки и техники, 2009)
The paper presents a survey of experimental methods for cyclotron production of ultrashort-lived (USL) and short-lived (SL) radionuclides recommended by the IAEA as most widely used in nuclear medicine. The data on radionuclide-producing nuclear reactions, the required energy range and targets are given. The undertaken analysis of experimental studies carried out at different scientific centers as well as the comparison with the parameters of the cyclotron CV-28 to be put into operation at the NSC KIPT suggest the conclusion about the operational capabilities of the isochronous cyclotron CV-28 to produce the mentioned radionuclides and the possibility of creating the positron-emission tomography (PET) with the CV-28 as the base. В роботі наведено огляд експериментальних методів одержання циклотронних ультракороткоживучих (УКЖ) та короткоживучих (КЖ) радіонуклидів, рекомендованих МАГАТЕ для найбільш широкого використання в ядерній медицині. Представлено дані про ядерні реакції, в яких вони одержуються, необхідний диапазон енергій, мішені для їх одержання. На основі проведеного аналіза експериментальних досліджень в різних наукових центрах і порівняння з параметрами циклотрона СV-28, який плануеться запустити в ННЦ ХФТІ, робиться висновок про реальні можливості наробки цих радіонуклидів на ізохронному циклотроні СV-28 та створення на його основі ПЭТ-центра для ядерної медицини. В работе дан обзор экспериментальных методов получения циклотронных ультракороткоживущих (УКЖ) и короткоживущих (КЖ) радионуклидов, рекомендованных МАГАТЭ как наиболее широко используемых в ядерной медицине. Представлены ядерные реакции, из которых они получаются, необходимый диапазон энергий, мишени для их получения. На основе проведенного анализа экспериментальных исследований в различных научных центрах и сравнения с параметрами циклотрона СV-28, который планируется запустить в ННЦ ХФТИ, делается вывод о реальной возможности наработки этих радионуклидов на изохронном циклотроне СV-28 и создания на его основе ПЭТ-центра для ядерной медицины.